Analysis Of The Quality of Human Resources in Preventing Fraud in The Management of Funds in Tondonggito Village, Southeast Wawonii District, Konawe Islands Regency - Yuana, Indira; Sabilalo, Mahmudin A.; Arqam, Muhammad; Halim, Ade Imam Muttaqien (AIBPM Publisher, 2025)
This study aims to find out and analyze the quality of human resources in preventing fraud in village fund managers in Tondonggito Village, Southeast Wawonii District, Konawe Islands Regency. This study uses a descriptive qualitative approach to primary data and secondary data, while the analysis units in this study are 5 people consisting of village heads, village treasurers, village secretaries and 2 community members. Techniques for data collection in research are observation, interviews and documentation. The results of the research conducted The intellectual ability of the village apparatus is still lacking and there is still a lot that needs to be improved, especially in the field of technology, but with cooperation and a good mindset makes the work done by the village apparatus completed on time. Words and Deeds.The quality of human resources in Tondonggito Village,Southeast Wawonii District, Konawe Islands Regency in preventing fraud in village fund management cannot be said to have good quality human resources to prevent fraud in village fund management